2010
DOI: 10.1108/09699981011038060
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to women in the UK construction industry

Abstract: Purpose -This paper aims to identify the main barriers that lead to the under-representation of women in the UK construction industry. The study, funded by ConstructionSkills, seeks to explore the issues that women face and investigate the potential positive impact that continuous professional development (CPD) may have upon improving the retention and career progression of women. Design/methodology/approach -The study uses an open-ended grounded theory (GT) approach, including 231 semi-structured questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 11 publications
1
45
0
1
Order By: Relevance
“…However, the findings indicate a very low female participation rate (6.67%). This fact supports various studies, as mentioned in the literature review, confirming that the construction industry is typically male-dominated (Agapiou, 2002;Loosemore et al, 2003;Worrall et al, 2010). In total, 68% of those interviewed had managed five or more construction projects in different airports.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…However, the findings indicate a very low female participation rate (6.67%). This fact supports various studies, as mentioned in the literature review, confirming that the construction industry is typically male-dominated (Agapiou, 2002;Loosemore et al, 2003;Worrall et al, 2010). In total, 68% of those interviewed had managed five or more construction projects in different airports.…”
supporting
confidence: 71%
“…Several studies (for example, Agapiou, 2002;Worrall et al, 2010) reported that this characteristic applies to almost every level of the construction sector from operational level, where site workers and other individuals operate on professional and managerial levels.…”
Section: Male-dominant Culturementioning
confidence: 99%
“…The gender composition of the sample was 135 male and 5 female participants. The proportion of women managers in the sample (about 4%) compares reasonably well with the total proportion of women employed in the Hong Kong construction sector (about 9%, see Hong Kong Census and Statistics Department, 2011) and in the construction sectors of other developed countries such as Australia (about 13%, see Francis, 2010) and the UK (about 10%, see Worrall et al, 2010). The survey and data examination procedures, as described below, provide further methodological and empirical reasons to believe that the analysis sample was not biased.…”
Section: Sample and Proceduresmentioning
confidence: 59%
“…| r | < 0.20) and statistically non-significant (p > 0.10), thus providing adequate proof that social desirability bias ("faking good") is not a problem in this study (Mitchell and Jolley, 2001). The proportion of women managers in the sample (about 4%) compares favorably with the total proportion of women employed in the Hong Kong construction sector (about 9%; Hong Kong Census and Statistics Department, 2011) and in the construction sectors of other developed countries such as Australia (about 13%; Francis, 2010) and the UK (about 10%; Worrall et al, 2010). The final analysis sample of 140 cases can, thus, be considered to be fairly representative of the target population and suitable for the subsequent analyses.…”
Section: Data Collection and Examination Proceduresmentioning
confidence: 83%